Exome sequencing of 85 Williams–Beuren syndrome cases rules out coding variation as a major contributor to remaining variance in social behavior. Issue 5 (15th July 2018) - Kopp, Nathan D.; Parrish, Phoebe C. R.; Lugo, Michael; Dougherty, Joseph D.; Kozel, Beth A.
Abstract: Background: Large, multigenic deletions at chromosome 7q11.23 result in a highly penetrant constellation of physical and behavioral symptoms known as Williams–Beuren syndrome (WS). Of particular interest is the unusual social‐cognitive profile evidenced by deficits in social cognition and communication reminiscent of autism spectrum disorders (ASD) that are juxtaposed with normal or even relatively enhanced social motivation. Interestingly, duplications in the same region also result in ASD‐like phenotypes as well as social phobias. Thus, the region clearly regulates human social motivation and behavior, yet the relevant gene(s) have not been definitively identified. Method: Here, we deeply phenotyped 85 individuals with WS and used exome sequencing to analyze common and rare variation for association with the remaining variance in social behavior as assessed by the Social Responsiveness Scale. Results: We replicated the previously reported unusual juxtaposition of behavioral symptoms in this new patient collection, but we did not find any new alleles of large effect in the targeted analysis of the remaining copy of genes in the Williams syndrome critical region. However, we report on two nominally significant SNPs in two genes that have been implicated in the cognitive and social phenotypes of Williams syndrome, BAZ1B and GTF2IRD1 . Secondary discovery driven explorations focusing on known ASD genes and an exome wide scan do not highlight any variants of a large effect. Conclusions: Whole exome sequencing of 85 individuals with WS did not support the hypothesis that there are variants of large effect within the remaining Williams syndrome critical region that contribute to the social phenotype. This deeply phenotyped and genotyped patient cohort with a defined mutation provides the opportunity for similar analyses focusing on noncoding variation and/or other phenotypic domains. Abstract : Williams syndrome is a neurodevelopmental disorder caused by a deletion of 1.5–1.8 Mbp on chromosome 7q11.23 that results in many phenotypes including manifestations of a hypersocial personality. Using whole‐exome sequencing, we investigated the effects of genetic variants on the remaining 7q11.23 allele on social behavior. We report on two nominally significant SNPs in BAZ1B and GTF2IRD1, which have been implicated in the cognitive phenotype of Williams syndrome and provide the largest genetic dataset on cases with Williams syndrome to the broader scientific community.